Environmental Requirements in the Field of Urban Development: Legal Land Aspects - Solomiya Kostyk (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the procedure for conducting an environmental impact assessment in the context of urban development activities in accordance with the Law of Ukraine "On Environmental Impact Assessment". The environmental impact assessment and the environmental expertise, which was carried out before the entry into force of the new legislation, were compared. Particular attention is devoted to public participation in the implementation of environmental impact assessment and to the introduction of a new information resource - the Unified Register of Environmental Impact Assessment.